Condom Usage Negotiation Among Customarily Married Women in Katlehong, Johannesburg. (January 2017) - Dube, Nkosiyazi; Nkomo, Thobeka S.; Khosa, Priscalia
South Africa has the highest number of HIV-infected people in the Southern African Region, and of great concern is the fact that cases of new infections among young people, especially young women and girls, are on the increase. The prevalence of HIV and deaths caused by AIDS are still on the increase, whereas condom use, particularly in rural areas, remains low. Consistent condom use is central to the prevention of unwanted pregnancies, HIV, and other sexually transmitted infections (STIs); yet, young men and women alike are hesitant to use condoms because of threats to their relationships, cultural roles, and, at times, economic survival. This study explored the views of customarily married housewives regarding condom use negotiation with their husbands. The findings point toward the need to empower women while they are still young so that they can be assertive, financially independent, and able to make their own decisions with regard to their sexuality.